2021
DOI: 10.3390/s21103486
|View full text |Cite
|
Sign up to set email alerts
|

Full-Self-Powered Humidity Sensor Based on Electrochemical Aluminum–Water Reaction

Abstract: A detailed examination of the principle of operation behind the functioning of the full-self-powered humidity sensor is presented. The sensor has been realized as a structure consisting of an interdigitated capacitor with aluminum thin-film digits. In this work, the details of its fabrication and activation are described in detail. The performed XRD, FTIR, SEM, AFM, and EIS analyses, as well as noise measurements, revealed that the dominant process of electricity generation is the electrochemical reaction betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Several major industries such as the chemical, pharmaceutical, and electronics industries have compulsory requirements to install humidity sensors to ensure product quality. [93] Most of the previous reported MEENGs' output performances have indicated a quasi-linear dependence on RH, so introducing higher RH is one of the generic strategies to enhance electricity generation. [48] However, many of these devices have a relatively high humidity threshold, which means that several types of MEENGs would not work under low RH.…”
Section: Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several major industries such as the chemical, pharmaceutical, and electronics industries have compulsory requirements to install humidity sensors to ensure product quality. [93] Most of the previous reported MEENGs' output performances have indicated a quasi-linear dependence on RH, so introducing higher RH is one of the generic strategies to enhance electricity generation. [48] However, many of these devices have a relatively high humidity threshold, which means that several types of MEENGs would not work under low RH.…”
Section: Sensorsmentioning
confidence: 99%
“…Several major industries such as the chemical, pharmaceutical, and electronics industries have compulsory requirements to install humidity sensors to ensure product quality. [ 93 ]…”
Section: Applications Assembled With Meengsmentioning
confidence: 99%
“…It was shown that this structure reacted in the presence of high humidity levels, close to 100% RH [31]. It was also proven [32] that the signal from this kind of structure was a consequence of the electrochemical reaction between aluminum and water on the surface of the sensor. In this work, the concept of a sensor based on activated aluminum is extended by adding electromagnetic (EM) harvesting and an electronic rectifier in order to modulate the output from the EM antenna.…”
Section: Introductionmentioning
confidence: 90%
“…The method of aluminum activation described here is a novel method, discovered and used for the first time for aluminum-battery-based sensor activation [31,32]. Other methods have been used for aluminum activation [42,43].…”
Section: Activationmentioning
confidence: 99%
See 1 more Smart Citation